Analisis Manajemen Proses pada Sistem Operasi Linux : Permasalahan dan Solusi - Muhammad Albedri; Yudha Purnama Putra; Elkin Rilvani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to analyze process management in the Linux operating system, focusing on how processes are managed from creation, scheduling, to termination. Linux utilizes various scheduling and memory management mechanisms to ensure system efficiency and stability. One of the schedulers used is the Completely Fair Scheduler (CFS), which provides a fair distribution of CPU time based on the priority and needs of the processes. This research also discusses the use of techniques such as paging for memory management and how Linux handles inter-process communication through pipes and shared memory. Experiments were conducted to measure CPU usage, memory consumption, and execution time by various processes with different priorities. The results show that Linux effectively manages resources, provides fair time-sharing, and maintains security by isolating the address space between the kernel and user-space. This study is expected to contribute to the further development of process management in Linux and provide insights for developers and system administrators to optimize operating system performance.